2014
DOI: 10.2147/trrm.s38620
|View full text |Cite
|
Sign up to set email alerts
|

Management of Candida infections in liver transplant recipients: current perspectives

Abstract: Liver transplantation has emerged as a widely accepted lifesaving therapeutic option for many patients with a variety of liver diseases. Improved surgical and medical management has led to significant improvements in post-transplant survival rates with a 1 year and 5 year patient survival of 87% and 73%, respectively. A high mortality rate due to infections during the first post-transplant year persists. Invasive candidiasis is recognized as a significant problem associated with high morbidity and mortality. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…IA in LTR are uniquely predisposed to dissemination of infection beyond the lungs, with >55% of patients having extrapulmonary manifestations. However, the clinical manifestations of IFIs can be non-specific because of immunosuppression and antifungal prophylaxis [45].…”
Section: Incidence and Epidemiology Of Invasive Fungal Infection In Lmentioning
confidence: 99%
See 1 more Smart Citation
“…IA in LTR are uniquely predisposed to dissemination of infection beyond the lungs, with >55% of patients having extrapulmonary manifestations. However, the clinical manifestations of IFIs can be non-specific because of immunosuppression and antifungal prophylaxis [45].…”
Section: Incidence and Epidemiology Of Invasive Fungal Infection In Lmentioning
confidence: 99%
“…In LTR, antifungal prophylaxis is selected in the early post-transplant period, during which the incidence of IC peaks. However, there is no consensus on the duration and choice of antifungal agent [45]. In LTR, 10 patients receive unnecessary antifungals to prevent one case of FI.…”
Section: Role Of Antifungal Stewardship (Afs)mentioning
confidence: 99%
“…Hussain et al [7], reported that the candidemia has been diagnosed in 40% of invasive candidiasis, median time of infection was 13.5 days and 78% of the infections were detected in first 3 months after transplantation. In our study, the candidemia was determined in 70% of LTRs within the first 3 months with a median of 29 days.…”
mentioning
confidence: 99%
“…The important point is to estimate which risk factors have contribution in candidemia development, obtaining blood culture from the patient and starting the treatment at the earliest. In fact, risk factors have been handled for invasive candidiasis of LTRs in many studies [7][8][9][10][11]. In these studies risk factors associated with candidemia have been reported as re-transplantation, preoperative creatinine level (≥ 2.0 mg/dl), need for renal replacement therapy within the first 30 days after transplantation, re-operation, choledochojejunostomy, the use of intraoperative blood products to more than 40 units, prolonged intraoperative time (≥ 11 hours), fulminant hepatic failure, candidemia and CMV co-infection and candida colonization in pre-transplantation period.…”
mentioning
confidence: 99%